The Determinants of Banking Profitability in Islamic and Conventional Banks: Evidence from Malaysia - Noor, Muhammad Sadi (2018)
This paper empirically examines the determinants of profitability of Islamic and conventional banks, within the Malaysian financial system, utilising data on 40 Malaysian banks over the 2010-2017 period. 16 of these are Islamic banks, 24 are conventional banks. The paper assesses whether similar determinants including bank-specific and external factors affect profitability. Return on assets is employed as a proxy for profitability. Bank-specific determinants include capital adequacy, liquidity, asset quality, expenses management, non-interest earnings assets to total assets and size. External determinants include, market concentration, GDP and inflation.